The Effect of Workload and Work Fatigue on Turnover Intention with Job Stress as an Intervening Variable - Eka Yulianti; Mulyana Mulyana (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
This research investigates how workload and work fatigue influence employees’ turnover intention, with job stress serving as a mediating factor, focusing on the Digital H3i Division of PT Indosat Tbk Semarang. Employing a quantitative approach with an explanatory design, the study involved 100 respondents chosen through a saturated sampling technique due to the limited and accessible population. Data were gathered using questionnaires and analyzed using Structural Equation Modeling (SEM) through the Partial Least Square approach in SmartPLS 4. The findings reveal that both workload and work fatigue significantly and positively affect job stress, which in turn significantly impacts turnover intention. Additionally, workload and work fatigue also directly and significantly influence employees’ intention to leave. Job stress acts as a key mediator linking workload and fatigue to turnover intention. These results suggest that increasing workload and fatigue elevate stress levels, which subsequently heighten employees’ desire to resign. The study highlights the need for PT Indosat Tbk’s management to ensure workload balance, allow adequate rest periods, and promote a supportive work environment to mitigate stress and reduce turnover. Proper stress management can help the company maintain a stable, motivated, and loyal workforce